(untitled) (Teacher’s World: Journal of Education and Research, 2024)
As part of a large research project, the present study reports the attitudes of university academics toward engaging in research and publication. A quantitative research method was employed to collect data from 347 university academics from five public universities in Bangladesh. An attitude survey scale and background questionnaire were administered. The findings revealed that university academics held positive attitudes towards research and publication. Significant variations were found based on gender and overseas qualifications as participants’ background variables. The research findings have promising implications for public universities, particularly in fostering an environment that is conducive to conducting high-quality research and publishing activities. Teacher’s World: Journal of Education and Research, 49 (2),151-172